EQUAL Fusariosis score 2021: An European Confederation of Medical Mycology score derived from current guidelines to measure QUALity of the clinical management of invasive fusariosis. Issue 12 (29th May 2021) - Guarana, Mariana; Nouér, Simone A.; Nucci, Marcio
Abstract: Background: Invasive fusariosis is a serious infection affecting mostly patients with haematologic malignancies and hematopoietic cell transplant recipients. Objectives: To develop a scoring tool that evaluates guideline adherence in the management of invasive fusariosis. Methods: We reviewed two guidelines, provided by the European Society for Clinical Microbiology and Infectious Diseases (ESCMID) and the European Confederation of Medical Mycology (ECMM), and selected the strongest recommendations for management quality as the bases for the scoring tool. Results: We reviewed the recommendations regarding primary and secondary prophylaxis, diagnostics procedures (images, blood cultures, biopsy of skin lesions with direct examination, culture and histopathology, species identification, antifungal susceptibility tests and antigen detection), treatment choices and follow‐up procedures. The tool comprises 18 items, with a maximum of 24 points. Conclusions: The EQUAL score Fusariosis is a tool that may help clinicians to measure guidelines adherence.